PENGARUH RASIO KEUANGAN LIKUIDITAS DAN AKTIVITAS TERHADAP HARGA SAHAM PERUSAHAAN FARMASI YANG GO PUBLIC DI BURSA EFEK INDONESIA - Marliza Noor Hayatie; Shela Puzi Dina (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
Financial statements are information that can help investors and other capital market players in identifying the condition of a company. A company is said to be successful and fulfills the company's goals by measuring the company's stock price. To find out the factors that influence the company's stock price, it is necessary to conduct a particular analysis. This research was conducted to determine the effect of independent variables consisting of liquidity and activity on the dependent variable, and to find out the independent variables that have a more dominant influence on stock prices. In this study, the authors used secondary data annual financial statements for a period of 3 years taken from the Indonesia Stock Exchange (IDX). The results showed that independent variables namely liquidity and activity had no significant effect on the dependent variable. The results of this study are expected to be able to help investors in comparing more diverse types of industries.